How big should the public capital stock be? The relationship between public capital and economic growth - David Alan Aschauer (Levy Economics Institute of Bard College, 1998)
Investment in infrastructure is necessary for a strong, flexible, and growing economy. However, the relationship between public capital and economic growth is not linear. At a certain level, the tax burden associated with financing and maintaining public capital reduces the returns to private industry, which in turn reduces growth; also, different types of spending have different effects on growth. The short- and long-term growth-maximizing effects of public investment increase as the ratio of public to private capital stock rises to an optimal level (found to be about 61 percent); above that level, the growth effects decrease. The public-to-private ratio is below the optimal level throughout much of the country and government spending is not always directed toward the types of investment that have the most positive effects on growth. Good economic policy requires both increasing the public capital stock and reorienting government spending from consumption to investment in physical capital stock.
Keywords: 330